EVALUASI PEMERIKSAAN CT SCAN THORAX TANPA KONTRAS DENGAN KLINIS TUBERCULOSIS PARU DI INSTALASI RADIOLOGI RUMAH SAKIT UMUM DAERAH AL IHSAN PEMPROV JABAR - -, Ardiana; Ardiana, Ardiana; Suwandi (JURNAL TERAS KESEHATAN, 2025)
Radiological imaging has an important role in diagnosis and detection of pulmonary tuberculosis.  The research aimed to determine the CT Scans of thorax in cases of pulmonary tuberculosis. The research method was a qualitative descriptive. Data collection was carried out by direct observation of examination process and  interview some radiologists, pulmonary specialists and four radiographers. There was a difference between theory and parameters at Al Ihsan Hospital. Using a scan slice thickness parameter of 0.75 mm because it iwas more detailed in viewing fine images of pulmonary tuberculosis, resulting in high detail. As well as using a low voltage of 100 kVp to ensure exposure to the dose received by the patient. The CT scan of thorax without contrast plays an important role in helping to confirm the diagnosis of pulmonary tuberculosis to see whether there were other lesions that can support the diagnosis of pulmonary tuberculosis.